2019
DOI: 10.1167/tvst.8.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compliance With Preoperative Posturing Advice and Head Movements on the Progression of Macula-On Retinal Detachment

Abstract: Purpose The aim of this study was to explore the relationship between compliance with preoperative posturing advice and progression of macula-on retinal detachment (RD) and to evaluate whether head positioning or head motility contributes most to RD progression. Methods Sixteen patients with macula-on RD were enrolled, admitted to the ward, and instructed to posture preoperatively. The primary outcome parameter was compliance, which was defined as the average head orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
6
0
7
Order By: Relevance
“…Preoperative posturing on the side where the RD mainly located is an effective strategy to reduce the progression of macula-on RD 28,29 . However, in our view, although macula detachment occurs in partial RD, preoperative posturing is still indispensable as the extent of detachment is positively related to the failure rate of RD repair 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative posturing on the side where the RD mainly located is an effective strategy to reduce the progression of macula-on RD 28,29 . However, in our view, although macula detachment occurs in partial RD, preoperative posturing is still indispensable as the extent of detachment is positively related to the failure rate of RD repair 30 .…”
Section: Discussionmentioning
confidence: 99%
“…De Jong et al. [ 4 ] concluded that limiting head and eye movements is enough to prevent RRD progression, but it should not be counted as an only contributing factor to SRRRD; the authors supposed that the gravitational force effect on the retina and subretinal fluid is small because of the no density difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…20 In particular, in patients with loss of central vision within one week, the height of macular elevation seems to be a stronger predictor for visual outcome than duration. 17,19 Preoperative posturing according to the location of the primary retinal break to prevent further accumulation and spreading of subretinal fluid to involve the macula has become an established procedure in patients with macula-on RD, [21][22][23][24] but not in patients in whom the macula is already detached.…”
mentioning
confidence: 99%
“…Preoperative posturing according to the location of the primary retinal break to prevent further accumulation and spreading of subretinal fluid to involve the macula has become an established procedure in patients with macula-on RD, 21–24 but not in patients in whom the macula is already detached.…”
mentioning
confidence: 99%